So sorry your grandma died. Get that paper in.": Graduate Teaching Assistants' Experiences of Student Grief in the Communication Classroom - Jessica Cherry; Carly Densmore (Central States Communication Association, 2024)
Graduate teaching assistants (GTAs) are faced with managing how to respond to student disclosures of grief in the classroom but often lack grief training from their universities when these instances occur. Good and Mad grief, and Critical Grief Pedagogy (CGP) are the frameworks for which this study is positioned. Through interviews with GTAs in the United States, we explore their experiences when engaging with student grief disclosures and revealed three main themes: regulations and boundaries, transactional exchanges in institutions, and the classroom being a human space. We also discuss how GTAs use CGP to manage these interactions. We further suggest that GTA training should include CGP to help prepare future instructors for student grief and welcome grief into the classroom.